Resistensi Dakwah Salafi terhadap Amal Usaha Muhammadiyah di Sidoarjo - Zaini Tamin AR; Riduwan Riduwan (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2020)
The infiltration of the Salafis into the Muhammadiyah organization became a continuing reality. This reality is driven by symptoms of the strengthening of the concept of salafism in the organization that founded by KH. Ahmad Dahlan. This study seeks to analyze the Salafi da’wah against the Charitable Business of Muhammadiyah in Taman, Sidoarjo, which is always resistant. This research uses a qualitative method with a naturalistic interpretive approach. The findings of this study reveal that Salafis offer "thinking" in every Muhammadiyah Business Charity institution in Sidoarjo. Salafis try to "dress" Muhammadiyah, but still have their mindset and ideology. With the thought movement, the Salafi propaganda model is carried out through infiltration, agitation, and propaganda within the Muhammadiyah Charitable Enterprises. This is not uncommon to cause resistance and even conflict between the two. The author recommends several efforts that must be made by the Muhammadiyah management: First, the power approach. The Muhammadiyah leadership must act firmly against Salafis through established rules. Second, the intellectual approach. This approach can be done by way of scientific dialogue in the public sphere, criticizing Salafis, as well as affirming the Muhammadiyah manhaj.